Effect of Stability and Funding Risk on Shariah Rural Bank's Profitability - Dyah Widhowaty Eko Purnomo Putri; Agus Widarjono (Universitas Airlangga, 2023)
ABSTRACT This study examined the effect of stability and funding risk, as well as bank-specific factors and macroeconomic variables, on Shariah Rural Bank's margin. We investigated 83 Shariah Rural Banks (SRBs) on the island of Java from 2017 to 2021 with quarterly data. We employed the dynamic panel data regression with the two-step system GMM method. Our study also splits SRBs into large and small SRBs. Our findings show that the stability and funding risk positively influence the margin. The CAR positively influences the margin but assets, CIR, and NPF are negatively associated with the margin. However, stability and funding risk can increase margin only for large SRBs. Our results imply that SRBs should increase their equity and mobilize their third party to improve their margin. In addition, SRBs should improve their operating efficiency and manage low financing risk. This research contributed to Islamic banking literature by including stability and funding risk in influencing margins. Keywords: Stability, funding risk, bank-specific variable, Margin, Shariah rural banks ABSTRAK Penelitian ini menganalisis pengaruh stabilitas dan resiko pendanaan serta faktor spesifik bank dan kondisi makroekonomi terhadap margin dari Bank Pembiayaan Rakyat Shariah (BPRS). Studi ini menganalisis BPRS di Jawa yang berjumlah 83 bank pada 2017-2021 dengan data kuartalan. Metode estimasi adalah regresi panel dinamis dengan metode two-step system GMM. Selanjutnya, studi ini membagi BPRS menjadi BPRS besar dan kecil. Hasilnya menunjukkan bahwa stabilitas dan resiko pendanaan berpengaruh positif terhadap margin. CAR berpengaruh positif sedangkan asset, CIR, dan NPF berpengaruh negatif terhadap margin. Namun, stabilitas dan resiko pendanaan berpengaruh terhadap margin hanya pada BPRS besar. Implikasinya, BPRS harus meningkatkan permodalan dan memobilisasi deposito supaya meningkatkan margin serta BPRS harus memperbaiki efisiensi dan mengurangi pembiayaan macet. Kontribusi penelitian adalah penggunaan variabel stabiltias dan resiko pendanaan di dalam mempengaruhi margin. Kata kunci: Stabilitas, Resiko pendanaan, Bank spesifik, Margin, BPRS.